Randomized experimental testing of new survey approaches to improve abortion reporting in the United States. Issue 4 (13th December 2022) - Lindberg, Laura D.; Maddow‐Zimet, Isaac; Mueller, Jennifer; VandeVusse, Alicia
Abstract: Context: Abortions are substantially underreported in surveys due to social stigma, compromising the study of abortion, pregnancy, fertility, and related demographic and health outcomes. Methods: In this study, we evaluated six methodological approaches identified through formative mixed‐methods research to improve the measurement of abortion in surveys. These approaches included altering the placement of abortion items in the survey, the order of pregnancy outcome questions, the level of detail, the introduction to the abortion question, and the context of the abortion question, and using graduated sensitivity. We embedded a preregistered randomized experiment in a newly designed online survey about sexual and reproductive health behaviors ( N = 6536). We randomized respondents to experimental arms in a fully crossed factorial design; we estimated an average treatment effect using standardized estimators from logistic regression models, adjusted for demographic covariates associated with reporting. Results: None of the experimental arms significantly improved abortion reporting compared to the control condition. Conclusion: More work is needed to improve reporting of abortion in future surveys, particularly as abortion access becomes increasingly restricted in the United States. Despite this study's null results, it provides a promising path for future efforts to improve abortion measurement. It is proof of concept for testing new approaches in a less expensive, faster, and more flexible format than embedding changes in existing national fertility surveys.